Ich bin auch ein Lemming: Herding and Consumption Capital in Arts and Culture - Dominic Rohner; Anna Winestein; Bruno S. Frey (Center for Research in Economics, Management and the Arts (CREMA), 2006)
Trends in arts and culture tend to be longer-lasting and less fragile than in other fields such as clothing design. Most herding models are not able to explain such stability, instead predicting informational cascades to be fragile and fads to be frequent. The present contribution is able to explain the hysterisis of trends in arts by incorporating the accumulation of consumption capital into a herding model. Further, the model is tested empirically by analyzing measures of relative and absolute concentration in the television business. It is concluded that by being exposed to art and culture people accumulate consumption capital for a particular style or artist and that this mechanism tends to make herding in arts stable over time.
Keywords: C11; D82; D83; Z11; 330; Art; Culture; Herding; Consumption Capital; Concentration